STRUKTUR KEPEMILIKAN DAN KOMPENSASI BONUS SERTA PENGARUHNYA TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2006-2010 - Evi Juliani Pujiati; Muhammad Arfan (Program Magister Akuntansi Unsyiah, 2013)
This research is aimed to investigate the influence of managerial ownership, institutional ownership, and bonus compensation, both simultaneously and partially, toward earnings management on listed companies from the manufacturing sector at the Indonesia Stock Exchange (ISX) for the year 2006-2010. The research type used is verificative research or hypothesis testing research. By using census method and unbalanced panel data, there are 77 firm observations fulfilling the population criteria.The data type used is secondary data gotten from the capital market reference center at the Indonesia Stock Exchange. The multiple regression analysis model is used to test the hypothesis.The results of this research show that (1) managerial ownership, institutional ownership, and bonus compensation simultaneously have influence toward earnings management (2) managerial ownership has negative influence toward earnings management (3) institutional ownership has negative influence toward earnings management, and (4) bonus compensation has negative influence toward earnings management. Keywords: managerial ownership, institutional ownership, bonus compensation, earnings management